ANALISIS PERBANDINGAN ALGORITMA ANTRIAN BERDASARKAN QOS PADA PENJADWALAN DI JARINGAN WIMAX - Azmuri Wahyu Azinar; Anjar Firmansya (Institut Teknologi Adhi Tama Surabaya)
At the moment, the development of communication technology is rapidly increased. WIMAX(Worldwide Interoperability for Microwave Access) is a wireless technology that provides a wide line a long distance. WIMAX provides a quality guarantee of QOS (Quality of Service)for different services in accordance with the QOS need. A Scheduling algorithm is required for the QOS needs. In this Sarjana thesis, the simulation of WIMAX network was performed by applying a scheduling algorithm namely FIFO(First In First Out), PQ(Priority Queuing), and WFQ (Weighted Fair Queuing) which were used for 35, 70, 103, 137, and 179 clients. The test result indicated that the lowest Delay value was 57.69% on FIFO algorithm with 137 clients, the lowest network load value was 86.46% on PQ algorithm with 179 clients, whilst the lowest Throughput value was 78.60% on PQ algorithm with 137 clients.